Цифро-аналоговые преобразователи c дельта-сигма модуляцией для систем связи пятого поколения - Матерухин, Сергей Евгеньевич (Методы и устройства передачи и обработки информации; № 24 (2022): Методы и устройства передачи и обработки информации, 2023)
This paper describes the main methods for constructing digital-to-analog converters based on delta-sigma modulation. The principles on which the delta sigma module is based are considered. The structure and principle of operation of digital-to-analog converters are described. The features of the construction of the main blocks are considered. The possibility of using digital-analog converters with delta-sigma modulation to increase the output frequency of the signal and the signal-to-noise ratio is evaluated.